"SERUM VITAMIN D AND HBA1C: A HIDDEN CONNECTION IN INDIAN TYPE 2 DIABETIC PATIENTS" - Ruchir Jain; Jaya Jain (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Vitamin D deficiency and poor glycemic control are common among Type 2 Diabetes Mellitus (T2DM) patients, particularly in India. While emerging evidence suggests a role of Vitamin D in glucose metabolism and insulin sensitivity, the relationship remains inconclusive. This study investigates the correlation between serum Vitamin D levels and HbA1c among T2DM patients. Objectives: To evaluate the association between serum 25-hydroxy Vitamin D levels and HbA1c in T2DM patients, and to assess its correlation with other metabolic parameters including fasting blood sugar (FBS), BMI, and lipid profile. Methods: A cross-sectional observational study was conducted from December 2023 to December 2024 at Index Medical College and Hospital, Indore. A total of 200 patients aged 30–70 years with a confirmed diagnosis of T2DM (≥6 months) were enrolled. Serum Vitamin D and HbA1c levels were measured using VIDAS Immunoassay and Bio-Rad D-10 analyzer, respectively. Correlation analysis was performed using Pearson’s coefficient, and multivariate regression was applied to control for confounding variables. Results: Among the 200 participants, 53% were female and 47% male. The mean Vitamin D level was ± 7.56 ng/mL, while the mean HbA1c was 8.72 ± 0.70%. A statistically significant inverse correlation was found between Vitamin D and HbA1c (r = -0.74, p < 0.05), as well as between Vitamin D and FBS (r = -0.54, p < 0.05). No significant correlation was observed between Vitamin D and BMI (r = -0.04) or total cholesterol (r = -0.15). Conclusion: This study demonstrates a significant negative correlation between Vitamin D levels and glycemic markers (HbA1c and FBS) in T2DM patients, suggesting a potential role for Vitamin D in improving glycemic control. Routine screening and correction of Vitamin D deficiency in diabetic patients may offer metabolic benefits.